PROBLEMS OF CLASSIFICATION OF ENGLISH AND UZBEKISTAN HUMOROUS TALES (Universal International Scientific Journal, 2026)
This article provides a comparative analysis of theoretical and methodological issues related to the classification of humorous tales in English and Uzbek oral folklore. The study highlights the genre characteristics of humorous tales, their borderline with household tales, anecdotes, and satirical narratives. The differences between the approaches to humor in English and Uzbek folklore traditions are identified, and the terminological inconsistency and the lack of uniformity of criteria in classification are indicated as the main problem. The article proposes a new classification approach based on the combination of functional, artistic, and social criteria, and justifies its methodological significance in comparative folklore. The results of the study serve as a theoretical basis for the systematic study of humorous tales as an independent and multi-layered folklore genre
Keywords: comic tales; folklore classification; comparative folklore